(untitled) (Informatica, 2022)
The construction industry is presently confronted with a myriad of issues which has necessitated the adoption of new technologies like the computerised accounting information system (CAIS) to keep up with the ever-changing construction environment. This research is aimed at empirically investigating the effect of CAIS contexts on construction companies’ performance (CCP), and the mediating effect of innovation on the relationship between CAIS and CCP. The data for this study were collected via a survey carried out using structured questionnaires. The questionnaires were self-administered. Non-probability sampling technique was used in this study for a population of 208 projects, and 152 usable responses were collected accounting for a 73% response rate. The collected data were analysed using descriptive statistics (mean score) and the partial least squares-structural equation modelling (PLS-SEM) method. The result of the study indicates that all the three CAIS contexts had insignificant effect on CCP, while the relationship between CAIS contexts and CCP is fully mediated by innovation. The findings of this study support the deduction that investing in CAIS processes while giving due attention to innovation within the organization improves construction companies’ performance. This study also, makes important recommendations for future research, alongside some practical and theoretical contributions.